An unvoiced complaint: an exploratory study of unifi complainers and non-complainers - Fairuz, Azmi Elmy; Ahmad, Jamilah (Diva Enterprises Pvt. Ltd., 2015)
This study was driven by the interest in marketing. It aimed to explore and better understand the responds styles of complainers, the factors affecting non-complainers to avoid complaining, and the personality traits of complainers and non-complainers. Many studies have been conducted in this area to understand the behaviour of complainers and non-complainers. However, most of these studies were carried out in the Western countries, and only few were conducted in Malaysia. This study aimed to understand why complainers lodge complaint and non-complainers did not voice any complaint to TM.